Rational Bases and Generalized Barycentrics Applications to Finite Elements and Graphics - Wachspress, Eugene (Springer International Publishing : Imprint: Springer, 2016)
This three-part volume explores theory for construction of rational interpolation functions for continuous patchwork approximation.  Authored by the namesake of the Wachspress Coordinates, the book develops construction of basis functions for a broad class of elements which have widespread graphics and finite element application. Part one is the 1975 book A Rational Finite Element Basis (with minor updates and corrections) written by Dr. Wachspress.  Part two describes theoretical advances since 1975 and includes analysis of elements not considered previously.  Part three consists of annotated MATLAB programs implementing theory presented in parts one and two.